Palliative care: a study on the experience of relatives of terminally ill cancer patients - Ordóñez Vázquez, Norma Alicia (2021)
Cancer is a multisymptomatic disease that affects a large part of the world's population and has been increasing in recent years. The experience of family caregivers provides information on the care and attention that the terminally ill person receives. Heidegger's hermeneutical phenomenology was proposed as an interpretive framework. The objective of this article was to know, from the reports of relatives, the medical, psychological, social and spiritual needs of patients with terminal cancer. 11 interviews were conducted. Transcripts were made and thematic analysis and the van Manen method were used. It was found that palliative care in the final stage of the disease is not provided in all cases. Priority is given to meeting medical needs that focus on pain control, leaving aside psychological, social and spiritual needs. The latter are resolved by the family itself. Comprehensive care for patients is necessary from various disciplines, always ensuring dignity and well-being at the end of life.